COVID-19 outbreak containment poises on the sensitivity and specificity of the quick COVID-19 tests - Sreedharan, Jayadevan; Muttappallymyalil, Jayakumary; Nair, Satish Chandrasekhar (International Journal Of Community Medicine And Public Health, 2020)
In the event of a pandemic such as COVID-19, past knowledge indicates that primordial prevention and primary prevention are imperative. Social distancing, respiratory etiquette, masking, and handwashing has proven to mitigate COVID-19 risk factors. Rampant population testing for COVID-19 will complement the prevention and is therefore at increased demand to identify and isolate those that may be asymptomatic and others that have recovered. Serology tests or the quick COVID-19 tests can help to identify exposure to a pathogen and the subsequent immune response.